ON THE NUMERICAL SIMULATION OF THE EFFECT OF VACCINE ON MEASLES USING VARIATIONAL ITERATION METHOD - Kolawole, Mutairu; Akin-Awoniran, Bukola O; Odeyemi, Kazeem A.; Adigun, Adepeju A.; Ibrahim, Musibau A.; Oladejo, Felix O. (JURNAL DIFERENSIAL, 2024)
The prevalence of measles as an infectious disease has been of major concern to the government health practitioners over the world. This paper intends to investigate the effect of vaccination as a control measure to control the incidence of it means. The basic reproduction number, local and global stabilities of the disease at equilibrium, sensitivity was obtained. The numerical simulation via variational iteration method was carried out. The result clearly shows that proper procurement of vaccine and its implementation is a good control strategy to reduce the rapid spread of the disease.